The VEGF receptor Flt-1 spatially modulates Flk-1 signaling and blood vessel branching - Kappas, Nicholas C. (The Rockefeller University Press, 2008)
Blood vessel formation requires the integrated regulation of endothelial cell proliferation and branching morphogenesis, but how this coordinated regulation is achieved is not well understood. Flt-1 (vascular endothelial growth factor [VEGF] receptor 1) is a high affinity VEGF-A receptor whose loss leads to vessel overgrowth and dysmorphogenesis. We examined the ability of Flt-1 isoform transgenes to rescue the vascular development of embryonic stem cell–derived flt-1(−/−) mutant vessels. Endothelial proliferation was equivalently rescued by both soluble (sFlt-1) and membrane-tethered (mFlt-1) isoforms, but only sFlt-1 rescued vessel branching. Flk-1 Tyr-1173 phosphorylation was increased in flt-1(−/−) mutant vessels and partially rescued by the Flt-1 isoform transgenes. sFlt-1–rescued vessels exhibited more heterogeneous levels of pFlk than did mFlt-1–rescued vessels, and reporter gene expression from the flt-1 locus was also heterogeneous in developing vessels. Our data support a model whereby sFlt-1 protein is more efficient than mFlt-1 at amplifying initial expression differences, and these amplified differences set up local discontinuities in VEGF-A ligand availability that are important for proper vessel branching.